Processing, microstructure, and tribological properties of WS2 reinforced aluminium metal matrix composite: laser powder bed fusion vs. spark plasma sintering - Li, Peifeng (2023)
Aluminium alloys hold great promise for automotive applications due to their lightweight. However, the inferior wear resistance of aluminium alloys limited their potential for automobile parts where the tribological performances of the material are greatly concerned. In the past few decades, a variety of aluminium metal matrix composites (MMCs) with enhanced wear resistance has been developed, with introducing ceramic or solid lubricants to the matrix being the most common strategy. Self-lubricating Al-based composites reinforced with solid lubricant WS2 promise to meet the demand for greener tribological parts. However, the interfacial reactions between Al and WS2 and their effect on the tribological performances by conventional methods had not been studied previously, and the design advantages granted by additive manufacturing (AM) processes coupled with their capacity for in-situ production of composite materials are yet to be exploited in the realm of Al-transition metal dichalcogenides composites.